Qualificação de mulheres de baixa renda: uma política feminista? Reflexões a partir do Pronatec Brasil Sem Miséria - Rombach, Melina (2014)
This dissertation problematizes the access of low-income women to vocational education, in which they are a minority. Vocational education is a state responsibility, and it has been an object of public policies since the creation of the first trade schools by President Getúlio Vargas, in the 1940s. This dissertation advances an analysis of Pronatec (National Program of Access to Professional Education and Employment), in its modality of “Workers’ Training Fellowship” (Bolsa Formação Trabalhador), implemented by the Ministry of Social Development since 2011. It does so by applying a gender perspective to the analysis of the program, but also attending to the challenges for its local implementation. The political importance of Pronatec—the most recent policy of its kind in Brazil—and its interesting institutional architecture make it a relevant case for the analysis of the challenges for its local implementation from a gender perspective. This study is based on the analysis of the experiences of implementation of “Pronatec Brasil Sem Miséria” in two municipalities of São Paulo Metropolitan Region: Suzano and Osasco. These municipalities are pioneers in the execution of the program in the state. I analyze both the discourses of federal bureaucrats and the materials produced by the federal government to regulate and guide the execution of the program at the municipal level, and the discourses of actors involved in its local implementation. This research identified the extent to which discourses at these different levels converged or diverged, regarding both the necessary agreements that are required for an effective implementation of the program, and the gender images that permeate the actions of the bureaucrats involved in both levels. Ultimately, these two dimensions condition the access of lowincome women to professional training.